Sanksi Adat Tentang Larangan Perkawinan Terhadap Orang Sesuku dengan Pelaku Zina - Rahmi, Nailur; Henny, Rinta Okta (Institut Agama Islam Negeri Curup, 2020)
The purpose of this study is to determine and describe the implementation of customary sanctions regarding the prohibition of marriage against people of the same ethnicity as adulterers and to analyze the views of Islamic law on customary sanctions regarding marriage rights against people of the same ethnicity as adultery. This type of research is field research, namely, research that is carried out in the field. The research data was collected through interviews with people affected by customary sanctions, niniak mamak, the head of KAN, and ulama. The data that had been collected were analyzed using a qualitative descriptive method. The results of the study found that the process of implementing customary sanctions regarding the prohibition of marriage against people of the same ethnicity as adulterers begins with the stipulation of customary sanctions against adulterers. If the sanctions are not implemented then the niniak mamak will prohibit the nephew from marrying until the sanctions are completed. The implementation of the prohibition of marriage to people who are of the same ethnicity as the perpetrator of adultery due to customary sanctions is not regulated in Islamic Law. These rules are the rules that apply in Nagari Lunto. including 'urf saheeh, because the conditions of' urf sahih have been fulfilled. Among the conditions is that it contains benefit and has been going on for a long time. The benefit of the implementation of the marriage prohibition due to the adultery customary sanction is to provide a deterrent effect on adultery in particular and the Lunto community in general so that they do not approach adultery anymore, and protect their nephews from things that deviate from Islamic teachings. Based on the Ê»urf method, the customary sanction regarding the prohibition of marriage against people of the same ethnicity as the perpetrator of adultery is permissible.